THE IMPACT OF MOTIVATION AND EMPLOYEE DEVELOPMENT ON EMPLOYEE PERFORMANCE AT KPKNL MANADO - Rumbay, Roland Willem (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Humans are always actives role in all activities inside the organization. They are planner, perpetrator and key factor to determine action to achieve the goals. The purpose of the company will be impossible to achieved without active participation of employees although they used a sophisticated tool in an organization activities. This study aims to motivation and employees development affect employees performance at Kantor Pelayanan Kekayaan Negara dan Lelang (KPKNL) Manado Simultaneously. The data used in this study is primary data obtained through the questionnaire distributed to employee in KPKNL Manado. The analytical method used was multiple linear regression analysis. Regression analysis shows the motivation and employee development have positive effect on performance in KPKNL Manado. The results of the F test (simultaneous hypothesis test) shows that motivation and employee development simultaneously affect the performance employee in KPKNL Manado. The result suggests Conduct supervision and evaluation to the performance of all employees. Because of the lack of performance evaluation of directors to assess the ability of an employee in terms of mastery of tasks, skills, responsibility. Keywords: motivation, employee development, employee performance